An Analysis of the Engagement Partner Busyness in Malaysia Pre- and Post- Establishment of the Audit Oversight Board - Wan Hussin, Wan Nordin; Bamahros, Hasan Mohammed; Shukeri, Siti Nonvahida (International Information Institute, 2016)
The audit market in Malaysia witnessed a significant change in 2010 with the establishment of the Audit Oversight Board (AOB) to promote confidence in the quality and reliability of the audited financial statements in Malaysia.The AOB has the power to inspect the audit working papers, and conduct inquiries and impose sanctions against non-compliance with the International Standards on Auditing, and other quality control standards. This study compares the annual and quarterly busyness of the signing audit partners in terms of the number of engagements pre- and post- establishment of the AOB.The finding indicates that there is a significant reduction in the number of multiple client engagements per signing partner following the establishment of AOB, suggesting that the incidence of overburdened engagement partners who may not devote sufficient time in directing audit effort and supe~sion has reduced.